Mechanisms of tertiary lymphoid structure formation: cooperation between inflammation and antigenicity - Khanal, Shrijan; Wieland, Andreas; Gunderson, Andrew J. (Frontiers in Immunology, 2023)
To mount an effective anti-tumor immune response capable of controlling or eliminating disease, sufficient numbers of lymphocytes must be recruited to malignant tissue and allowed to sustain their effector functions. Indeed, higher infiltration of T and B cells in tumor tissue, often referred to as "hot tumors", is prognostic for patient survival and predictive of response to immunotherapy in almost all cancer types. The organization of tertiary lymphoid structures (TLS) in solid tumors is a unique example of a hot tumor whereby T and B lymphocytes aggregate with antigen presenting cells and high endothelial venules reflecting the cellular organization observed in lymphoid tissue. Many groups have reported that the presence of preexisting TLS in tumors is associated with a superior adaptive immune response, response to immunotherapy, and improved survivorship over those without TLS. Accordingly, there is significant interest into understanding the mechanisms of how and why TLS organize so that they can be elicited therapeutically in patients with few or no TLS. Unfortunately, the most commonly used mouse models of cancer do not spontaneously form TLS, thus significantly restricting our understanding of TLS biology. This brief review will summarize our current state of knowledge of TLS neogenesis and address the current gaps in the field.